2014
DOI: 10.5588/ijtld.13.0044
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in the intensive care unit: a prospective observational study

Abstract: The mortality of TB patients admitted to the ICU was extremely high. Very few parameters were associated with poor outcome, and no single parameter predicted both ICU and in-patient mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 24 publications
5
60
5
Order By: Relevance
“…This is in line with the described worse TB outcome in hospitalized patients [32,33]. However, in-hospital mortality due to PTB seems underestimated, when those who require advanced respiratory support face a much higher death rate (up to 70%) than subjects with respiratory failure due to other causes [34].…”
Section: Discussionsupporting
confidence: 66%
“…This is in line with the described worse TB outcome in hospitalized patients [32,33]. However, in-hospital mortality due to PTB seems underestimated, when those who require advanced respiratory support face a much higher death rate (up to 70%) than subjects with respiratory failure due to other causes [34].…”
Section: Discussionsupporting
confidence: 66%
“…[2] A simple severity-of-illness score, based on our published dataset as well as other known poor prognostic factors, was subsequently retrospectively applied to the study population's admission data in order to assess its validity.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…[1,2] Previous studies have shown that approximately 1.5% of adults being treated for active TB in academic hospitals develop respiratory failure requiring admission to an intensive care unit (ICU). [3] The mortality rate of patients with acute respiratory failure due to TB is higher than that of patients with respiratory failure due to other causes, and ranges from 40% to 80%.…”
mentioning
confidence: 99%
See 2 more Smart Citations